A Semantic Analysis of the Concept of 'Love' in Indonesian: A Comparative Study with English - Lihardo Manik; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
The concept of “love” is complex and culturally variable, posing challenges for cross-linguistic understanding and translation. This study aims to conduct a semantic analysis of the concept of “love” in Indonesian (cinta) compared to English, to reveal both universal and culture-specific meanings. Using a qualitative approach, the research integrates lexical semantics, collocational analysis, and conceptual metaphor theory to examine dictionary definitions, corpus data, and metaphorical expressions in both languages. The findings show that while both languages share a core meaning of deep affection, Indonesian cinta has a broader semantic scope including spiritual and patriotic dimensions, reflecting Indonesia’s collectivist values. English love predominantly denotes individualistic romantic feelings. Metaphorical analysis further highlights distinct cultural conceptualizations: English metaphors emphasize agency and conflict, whereas Indonesian metaphors focus on growth and unity.